Applying a Self-Made Automobile Heterodyne Interferometer to Measure the Parameters of Twisted Nematic Liquid Crystal - Shinn-Fwu Wang; Pei-Cheng Ke; Wesley Lai; Hao Ma; Yi-Zhan Su; Jyh-Shyan Chiu (Advances in Condensed Matter Physics)
A self-made automobile heterodyne interferometer with a closed control loop is presented. In addition, we will apply the self-made automobile heterodyne interferometer to measure the parameters of optically compensated twisted nematic liquid crystal (TN LC). It is worthy to be mentioned that the self-made automobile heterodyne interferometer has a compact size because all the optical components are installed in the mechanism of the system. Besides, the self-made automobile heterodyne interferometer has some much more merits, for example, automobile control, a simple setup, in real-time test, reliability, and so forth. Besides, it is very stable because of its common optical path insensitive to environmental disturbances. And its feasibility is demonstrated.